The PEMANFAATAN SMART FARMING MELALUI FIELD MONITORING SYSTEM UNTUK PERTANIAN BERKELANJUTAN DI KABUPATEN SUMENEP - Rahman, Sindi Arista; Wilda Rasaili; Ach Andiriyanto; Deny Feri Suharyanto; Zarnuji (LPPM UNINUS, 2024)
Agriculture is a strategic sector in meeting food needs and significantly impacts people's lives. For the agricultural sector to always grow productively, it is very necessary to modernize agriculture by utilizing technological aspects. Increasing agricultural needs and extreme weather fluctuations make it imperative for agricultural aspects to carry out reforms. So this service activity is to explain to the farmer group community about the use of smart farming through a field monitoring system. The method used is qualitative with 4 stages, 1) preparation: coordination, study, and creation of materials, 2) implementation: lectures, visualization, discussions, and collaboration mapping, 3) evaluation: community understanding, and encouragement from the village government, 4) reporting: report manuscripts and publications. The results that can be obtained from this activity are the socialization and education of agricultural technology through the use of smart farming. The community has high enthusiasm and a high spirit of reform but has weaknesses in human and financial resources. So the results of this PkM activity also recommend the openness of the Somor Sokon farmer group to the minds of young people and the awareness of young people to be involved in the development of village agriculture. It is also recommended to collaborate with the village government in providing financial resources and facilities related to smart farming Keywords: Agriculture, Smart Farming, Field Monitoring System, Sustainability